(untitled) (Research, Society and Development, 2022)
The article presented here has as its central subject the discussion around the new Brazilian Civil Procedure Code of 2015, which, in order to speed up the process, adopted, among other measures, a list of restricted and exhaustive possibilities to attack through from the interlocutory appeal, interlocutory decisions in the cognitive phase of the processes. It happens that in specific situations, not foreseen in that list of article 1015, the useful result of the process can be lost, which has put the higher courts in a position to mitigate such taxation. This work aims to demonstrate such situations and the way that the courts have acted, to minimize social losses that may occur, if such mitigation is not carried out. Using inductive and systemic methods, it is intended to verify if the legislator could have better elaborated the device, given the impact on the legal environment. It is concluded that the jurisprudence, the superior courts and the doctrine will have an essential role in the construction of a way to adapt the use of the device to the national legal reality.